The Effect of Intellectual Capital and Sustainability Report on Firm Value Mediated by Financial Performance - Mohammad Sakti Qudratulloh; Desmiza Desmiza (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to examine the impact of intellectual capital, as measured by the proxy VAIC (Value Added Intellectual Coefficient), and sustainability report, as measured by the proxy SRDI (Sustainability Report Disclosure Index), on firm value (Tobin's Q), as mediated by financial performance (ROA) in companies listed on the LQ45 Index from 2018 to 2022. This study employs quantitative methods. With a study sample of 15 firms, the purposive sampling approach was employed to choose samples. Secondary data taken from the company's annual report and sustainability report, obtained 75 processed data, was utilized. With the assistance of Eviews 12 software, this study employs path analysis and panel data regression. The results showed that partially intellectual capital and sustainability report have no effect on firm value, ROA has a positive effect on firm value, and simultaneously intellectual capital, sustainability report, and ROA have a significant effect on firm value. Furthermore, both partially and simultaneously intellectual capital and sustainability report have a positive effect on ROA. The results of this study also show that ROA is not able to mediate the relationship between intellectual capital and sustainability report on firm value. Keywords: Intellectual Capital, Sustainability Report, Financial Performance, Firm Value